Investigação Química e Biológica de Bauhinia cheilantha (Bong.) Steud - Silva, Ana Maria Amaral (2018)
The present work reports the chemical and biological study of the fresh leaves essential oil (OEBC) and the ethanolic extract from the roots of Bauhinia cheilantha (EEBCR). The essential oil (OEBC) has been obtained by hydrodistillation, and 97.84% of its constituents were identified. (E)-cariophilene (21.65%) and α-pinene (11.74%) were the major constituents. The study of the fixed constituents resulted in the isolation and structural determination of nine secondary metabolites: the oxepinic derivatives pacharina (BCR-1) and bauhiniastatin 1 (BCR-2), the triterpenes cycloartenone (BCR-3) and taraxerol (BCR-6), the flavonoids fisetinidol (BCR-5) and the mixture of dihydroquercetin and 2-(3',4'-dihydroxyphenyl)-5-methoxychroman-3,7-diol (BCR-4) and the bibenzis 3,5-dimethoxy- 4-methyl-2'-hydroxybibenzyl (BCR-7) and 3,5,6-trimethoxy-4-methyl-2'-hydroxybibenzyl (BCR-8). It is noteworthy that BCR-3 is being described for the first time in the Bauhinia genus and BCR-8 is being reported for the first time in the literature. Structures of isolated secondary metabolites were elucidated by 1 H and 13 C NMR, IR and MS, together with the comparison with the data described in the literature. The hexane (FHBCR), dichloromethane (FDBCR), ethyl acetate (FABCR) and methanolic (FMBCR) fractions, obtained from the chromatographic treatment of the ethanolic extract from roots (EEBCR), as well as the essential oil of the fresh leaves of B. cheilantha (OEBC) were evaluated for their cytotoxicity on human tumor cell lines HL-60 (promyelocytic leukemia), NCI-H292 (lung carcinoma) and MCF-7 (breast carcinoma), and IC50 values were obtained with their respective confidence intervals 8.6 (5.9 – 12.6), 33.08 (29.1 – 37.5), and 18.3 (16.0 – 21.0) for the OEBC and 7.6 (6,1 – 9.4), 5.4 (4.2 – 6.9) and 2.7 (1.9 – 3.7) for FDBCR, the active samples. The ethanolic extract from roots (EEBCR), the four fractions mentioned (FHBCR, FDBCR, FABCR and FMBCR) and essential oil (OEBC) were submitted to evaluation of the activity on third stage larvae of Aedes aegypti, however, only the essential oil (OEBC) showed to be active, with a LC50 value corresponding to 40.84 ± 0.87 μg / mL.